PENGARUH PERKEMBANGAN PERKEBUNAN KELAPA SAWIT TERHADAP PEMBANGUNAN EKONOMI PEDESAAN DI DESA PASIR KERANJI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Susanti, Lani; Syahza, Almasdi; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this his study aimed to analyze the effect of the development of oil palm plantations on rural economic development in Pasir Pasir Penyu Keranji Indragiri Hulu. This research was conducted in the village of Pasir Pasir Penyu Keranji Indragiri upstream from March 2016 to the finishes. The research method is descriptive method. The study population by 83 people and the entire population as respondents in this study. Data collection instrument used was a questionnaire. Data analysis technique used is descriptive qualitative. The result showed that the activity of oil palm plantations in the village of Pasir Pasir Penyu Keranji Indragiri Hulu creates a multiplier effect of 1.03, especially in employment and business opportunity. Economically will create purchasing power in Pasir Pasir Penyu Keranji Indragiri Hulu, which in turn increases the demand for public goods.Keywords: Multiplier effect, Rural Economic Development, Oil Palm Plantations